PS36 Probation and NHS Working Together to Reduce Health Inequalities: Great Expectations or a Tale of Two Services. (17th September 2012) - Parkes, J; Roderick, P; Panozzo, S
Abstract : Background: Offenders within the community are considered a socially excluded population experiencing poorer health than the general population and difficulties in accessing health care. There is little research focused on Community based offenders supervised by Probation. This study explored probation staff's knowledge, perceptions and attitudes to offender health needs and access to health services. Methods: Using information derived from qualitative research with probation staff and following a pilot, a national on-line questionnaire survey was conducted of probation staff involved in the management of offenders from a geographically representative sample of Probation Trusts in England and Wales. The questionnaire covered: offender health issues, enablers and barriers to health service access, and the NHS/CJS partnership. Models of good/innovative practice were sought. Results: Sixteen Probation Trusts participated and 611/2810 (22%) responses were obtained. 72% were female, 58% had 6–15 years of experience in probation service. The main offender health issues were substance misuse, mental health (MH), learning disabilities and chronic disease, with alcohol misuse the most important. Provision of easily accessible mental health (for mild –moderate severity) and alcohol treatment services were considered to be inadequate (often/occasional lack of adequate provision 65% alcohol treatment vs 42% drug treatment vs 90% MH). The main barrier reported was poor communication between probation and the NHS in particular with Primary Care services. It was felt that many offenders had not registered with a GP and that there was little joint working, understanding and education between primary care and probation. In addition the chaotic lifestyle of offenders lead to them having difficulties in negotiating health services and having appropriate health seeking behaviours, often accessing health services at a point of crisis (A&E). Responsiveness of health services was perceived to be lacking. Provision of in-house services (particularly mental health) was considered to be very useful where available. Suggested improvements included undertaking health needs assessments to inform joint strategic planning, focus on improvement of alcohol treatment provision; joint education sessions for GPs and Offender Managers, exploration of in-house mental health services; increased access to health trainers, and greater health focus in probation staff training. Conclusion: Probation staff participants were very supportive of improving health of offenders. This study identified some key barriers to addressing the health needs of offenders and their access to services, with practical solutions identified by participants providing implications for policy within the 'new' NHS, health service commissioning, and future research.